THE EFFECTIVENESS OF PROTECTIVE POWER OF STARFRUIT (Averrhoa bilimbi) JUICE IN CATFISH AGAINST MOTILE AEROMONAS SEPTICEMIA DISEASES - Sefti Heza Dwinanti; Ratu Brata T. Mengkrin; Ade Dwi Sasanti (Aquaculture Department, University of Mataram, 2021)
Starfruit contains active ingredients such as flavonoids, phenols, antioxidants and vitamin C so that it can be used as an immunostimulant in catfish farming activities. Motile Aeromonas Septicemia (MAS) is one of the obstacles that can cause catfish farming losses. This study aims to determine the effect of differences in timing of feeding containing starfruit juice to protect catfish from MAS disease. The study was designed using a completely randomized design (CRD) consisting of 6 treatments (P) in the form of feeding duration containing starfruit for 7 days (P1), 14 days (P2), 21 days (P3), 28 days (P4). and 35 days (P5) and control of feeding without star fruit juice (P0). The research was carried out at the Aquaculture Laboratory, Sriwijya University. The dose of star fruit juice mixed in the feed is 300 mL.Kg-1 while the catfish used is 8-12 cm in size. The challenge test used Aeromonas hydrophilla bacteria with a density of 108 CFU.mL-1 which was injected as much as 0.5 mL.tail-1 intramuscularly. The results showed that administration containing starfruit juice for 28 days provided the best protection. Based on the hematological test the day before and before infection, the delta decreased the hematocrit by 3% and the delta decreased the erythrocyte count by 3,103 cells.mL-1. In addition, live feed after infection was 100%, prevalence was 17.78% and there was no effect of giving starfruit juice on growth and feed efficiency.